Enhancement of Non-photochemical Quenching as an Adaptive Strategy under Phosphorus Deprivation in the Dinoflagellate Karlodinium veneficum - Cui, Yudong; Zhang, Huan; Lin, Senjie (Frontiers in Microbiology, 2017)
Intensified water column stratification due to global warming has the potential to decrease nutrient availability while increasing excess light for the photosynthesis of phytoplankton in the euphotic zone, which together will increase the need for photoprotective strategies such as non-photochemical quenching (NPQ). We investigated whether NPQ is enhanced and how it is regulated molecularly under phosphorus (P) deprivation in the dinoflagellate Karlodinium veneficum. We grew K. veneficum under P-replete and P-depleted conditions, monitored their growth rates and chlorophyll fluorescence, and conducted gene expression analyses and comparative proteomic analysis. The results were used to characterize NPQ modulation and associated gene expression dynamics under P deprivation. We found that NPQ in K. veneficum was elevated significantly under P deprivation. Accordingly, the abundances of three light-harvesting complex stress-related proteins increased under P-depleted condition. Besides, many enzymes related to genetic information flow were down-regulated while many enzymes related to energy production and conversion were up-regulated under P deprivation. Taken together, our results indicate that K. veneficum cells respond to P deprivation by reconfiguring the metabolic landscape and up-tuning NPQ to increase the capacity to dissipate excess light energy and maintain the fluency of energy flow, which provides a new perspective about what adaptive strategy dinoflagellates have evolved to cope with P deprivation.